Jacobian Elliptic Functions - 23.2 Definitions and Periodic Properties

From testwiki
Jump to navigation Jump to search


DLMF Formula Constraints Maple Mathematica Symbolic
Maple
Symbolic
Mathematica
Numeric
Maple
Numeric
Mathematica
23.2.E1 Ο‰ 1 + Ο‰ 2 + Ο‰ 3 = 0 subscript πœ” 1 subscript πœ” 2 subscript πœ” 3 0 {\displaystyle{\displaystyle\omega_{1}+\omega_{2}+\omega_{3}=0}}
\omega_{1}+\omega_{2}+\omega_{3} = 0

omega[1]+ omega[2]+ omega[3] = 0
Subscript[\[Omega], 1]+ Subscript[\[Omega], 2]+ Subscript[\[Omega], 3] == 0
Skipped - no semantic math Skipped - no semantic math - -
23.2#Ex1 Ο‡ 1 = a ⁒ Ο‰ 1 + b ⁒ Ο‰ 3 subscript πœ’ 1 π‘Ž subscript πœ” 1 𝑏 subscript πœ” 3 {\displaystyle{\displaystyle\chi_{1}=a\omega_{1}+b\omega_{3}}}
\chi_{1} = a\omega_{1}+b\omega_{3}

chi[1] = a*omega[1]+ b*omega[3]
Subscript[\[Chi], 1] == a*Subscript[\[Omega], 1]+ b*Subscript[\[Omega], 3]
Skipped - no semantic math Skipped - no semantic math - -
23.2#Ex2 Ο‡ 3 = c ⁒ Ο‰ 1 + d ⁒ Ο‰ 3 subscript πœ’ 3 𝑐 subscript πœ” 1 𝑑 subscript πœ” 3 {\displaystyle{\displaystyle\chi_{3}=c\omega_{1}+d\omega_{3}}}
\chi_{3} = c\omega_{1}+d\omega_{3}

chi[3] = c*omega[1]+ d*omega[3]
Subscript[\[Chi], 3] == c*Subscript[\[Omega], 1]+ d*Subscript[\[Omega], 3]
Skipped - no semantic math Skipped - no semantic math - -
23.2.E3 a ⁒ d - b ⁒ c = 1 π‘Ž 𝑑 𝑏 𝑐 1 {\displaystyle{\displaystyle ad-bc=1}}
ad-bc = 1

a*d - b*c = 1
a*d - b*c == 1
Skipped - no semantic math Skipped - no semantic math - -
23.2.E13 Ξ· 1 + Ξ· 2 + Ξ· 3 = 0 subscript πœ‚ 1 subscript πœ‚ 2 subscript πœ‚ 3 0 {\displaystyle{\displaystyle\eta_{1}+\eta_{2}+\eta_{3}=0}}
\eta_{1}+\eta_{2}+\eta_{3} = 0

eta[1]+ eta[2]+ eta[3] = 0
Subscript[\[Eta], 1]+ Subscript[\[Eta], 2]+ Subscript[\[Eta], 3] == 0
Skipped - no semantic math Skipped - no semantic math - -
23.2.E14 Ξ· 3 ⁒ Ο‰ 2 - Ξ· 2 ⁒ Ο‰ 3 = Ξ· 2 ⁒ Ο‰ 1 - Ξ· 1 ⁒ Ο‰ 2 subscript πœ‚ 3 subscript πœ” 2 subscript πœ‚ 2 subscript πœ” 3 subscript πœ‚ 2 subscript πœ” 1 subscript πœ‚ 1 subscript πœ” 2 {\displaystyle{\displaystyle\eta_{3}\omega_{2}-\eta_{2}\omega_{3}=\eta_{2}% \omega_{1}-\eta_{1}\omega_{2}}}
\eta_{3}\omega_{2}-\eta_{2}\omega_{3} = \eta_{2}\omega_{1}-\eta_{1}\omega_{2}

eta[3]*omega[2]- eta[2]*omega[3] = eta[2]*omega[1]- eta[1]*omega[2]
Subscript[\[Eta], 3]*Subscript[\[Omega], 2]- Subscript[\[Eta], 2]*Subscript[\[Omega], 3] == Subscript[\[Eta], 2]*Subscript[\[Omega], 1]- Subscript[\[Eta], 1]*Subscript[\[Omega], 2]
Skipped - no semantic math Skipped - no semantic math - -